2011
DOI: 10.1007/s10711-011-9601-4
|View full text |Cite
|
Sign up to set email alerts
|

On local comparison between various metrics on Teichmüller spaces

Abstract: International audienceThere are several Teichmüller spaces associated to a surface of infinite topological type, after the choice of a particular basepoint ( a complex or a hyperbolic structure on the surface). These spaces include the quasiconformal Teichmüller space, the length spectrum Teichmüller space, the Fenchel-Nielsen Teichmüller space, and there are others. In general, these spaces are set-theoretically different. An important question is therefore to understand relations between these spaces. Each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…In the same paper, Shiga showed that if the hyperbolic metric R carries a geodesic pants decomposition that satisfies Shiga's condition, then d ls and d qc induce the same topology on T qc (R). In the paper [4] we strengthened this result by showing that under Shiga's condition the inclusion map is locally bi-Lipschitz.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the same paper, Shiga showed that if the hyperbolic metric R carries a geodesic pants decomposition that satisfies Shiga's condition, then d ls and d qc induce the same topology on T qc (R). In the paper [4] we strengthened this result by showing that under Shiga's condition the inclusion map is locally bi-Lipschitz.…”
Section: Introductionmentioning
confidence: 84%
“…Then we proved that d qc (X, X i ) → ∞, while d ls (X, X i ) → 0. If we set Y n = τ tn αn • · · · • τ t2 α2 • τ t1 α1 (X) and if we define Y ∞ to be the surface obtained from X by a twist of magnitude t i along α i for every i, then a similar argument shows that Y ∞ ∈ T ls (R) \ T qc (R) and lim n→∞ d ls (Y n , Y ∞ ) = 0; see [3], [4] for more details. We shall give another proof of the last result in Section 5 below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for surfaces of infinite topological type, Teichmüller space can be defined, using either pants decompositions, complex structures, or length-spectrum. But these definitions may yield different spaces as show in [ALP + 11, ALPS12b] and [ALPS12a].…”
Section: Introductionmentioning
confidence: 99%
“…For a hyperbolic Riemann surface R 0 , consider a pair (R, f ) of a Riemann surface R and a quasiconformal mapping f from R 0 to R. Such pairs (R 1 , f 1 ) and (R 2 , f 2 We introduce another metric on T (R 0 ). Let C(R 0 ) be the set of non-trivial and non-peripheral closed curves in R 0 .…”
Section: Introductionmentioning
confidence: 99%